Method for producing carboxymethylcellulose particles, carboxymethylcellulose particles produced by said method, and absorbent articles containing the same
The core-shell structured CMC particles, produced through a core and surface crosslinking process, address uniformity and absorption challenges in cellulose-derived superabsorbents, offering enhanced gel strength and blood absorption.
Patent Information
- Application Number
- JP2021552666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-04
- Filing Date
- 2020-03-04
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-03-04
Smart Images

Figure 0007605746000002 
Figure 0007605746000003 
Figure 0007605746000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing carboxymethyl cellulose (hereinafter referred to as "CMC") particles, CMC particles produced by the method, and absorbent articles containing the same. More specifically, the present invention relates to a method for producing CMC particles, which includes a step of reacting a CMC crosslinked body that has undergone a core crosslinking reaction step with a surface crosslinking agent to obtain CMC having a core-shell structure, CMC particles produced by the method, and absorbent articles containing the same. [Background technology]
[0002] Superabsorbent polymers (hereinafter referred to as "SAP") are functional materials that can absorb tens to thousands of times their own weight in water, and are widely used as materials for absorbent articles such as baby diapers, hygiene products such as sanitary napkins for women and urinary incontinence products for adults, pet care products such as defecation pads, medical absorbents, waterproofing materials for civil engineering and construction, seedling sheets, and freshness-maintaining agents in the food distribution field.
[0003] Since the SAP is mainly used as a disposable material, it must be easy to manufacture and have a low unit price, and important physical properties include the ability to absorb water from a substrate containing an aqueous liquid, liquid permeability, and strength of the swollen gel.
[0004] In the past, acrylic absorbent resins have been commonly used as SAPs due to their high absorbency and low processing costs. However, acrylic absorbent resins are materials obtained from the petroleum industry and may be toxic due to residual monomers, and therefore have the disadvantage that they may cause erythema and pruritus on body parts that come into contact with them for long periods of time when used in diapers and sanitary products. Therefore, research has been conducted into a method of manufacturing CMC derived from cellulose, a natural plant material, into highly absorbent particles and applying them to absorbent products.
[0005] As one such conventional method, Patent Document 1 (Korean Patent Publication No. 2001-0105311) describes a method for producing a highly absorbent polysaccharide derivative, which includes the steps of (a) cross-linking one or more polysaccharides containing acidic groups, such as CMC, with a cross-linking agent to produce a gel, (b) adjusting the pH of the polysaccharide to a value of 3.5 to 5.5, if necessary, (c) pulverizing the acidified polysaccharide gel, and (d) drying the pulverized polysaccharide at high temperature.
[0006] The patent document 1 states that the highly absorbent polysaccharide derivatives can be used to absorb liquids consisting of body fluids containing various salts and nonionic substances, and are particularly suitable for the manufacture of absorbent sanitary articles such as diapers and sanitary napkins. In practice, the highly absorbent polysaccharide derivatives are mainly used as absorbent materials for diapers for absorbing urine. However, since the absorbency of blood is relatively low, it is difficult to apply them to feminine products for absorbing blood. This is because the physical properties of urine and menstrual blood are very different. Specifically, menstrual blood contains water, salt, protein, cells, etc., and therefore has a higher viscosity than urine and a very slow diffusion rate. In addition, large cell masses contained in blood are not absorbed by existing SAPs such as the highly absorbent polysaccharide derivatives, and form a film on the surface to prevent blood from being absorbed.
[0007] As a method for solving such problems, Patent Document 2 (JP Patent Publication No. 2005-263858) describes a method for producing an absorbent material, which includes (i) a step of providing an aqueous solution containing a polyvalent metal ion and a surfactant, (ii) a step of adding a cellulose derivative and / or alginic acid or a salt thereof to the aqueous solution, and then crosslinking and simultaneously swelling and hydrating the aqueous solution to form a gel, (iii) a step of contacting the crosslinked gel obtained in step (ii) with a hydrophilic volatile solvent to dehydrate it, and (iv) a step of drying. At this time, the method for producing the absorbent material further includes a step of treating the solid obtained in step (iii) or step (iv) with a surface crosslinking agent.
[0008] Referring to the examples of Patent Document 2, CMC powder is used as the cellulose derivative and / or alginic acid or its salt, and the CMC powder is added to the aqueous solution provided by the step (i) to swell and crosslink to obtain a crosslinked gel. However, according to the method, the CMC powder rapidly absorbs water and swells at the beginning of the step (ii) to obtain the crosslinked gel, resulting in high viscosity, which may cause a non-uniform crosslinking reaction. In addition, when considering the wearing comfort when applied to feminine sanitary napkins and adult urinary incontinence products, there is still a need to improve the blood absorption and water retention of absorbents. In addition, the pressure absorption capacity, which measures the degree to which physiological saline is absorbed under pressure, is also a factor that may affect the wearing comfort, so there is also a need to improve this. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] KR1020010105311 A [Patent Document 2] JP2005263858A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention is intended to solve the above problems, and aims to provide a method for producing CMC particles having excellent blood absorption capacity, centrifuge retention capacity (CRC) and absorbency under load (AUL), by reacting a CMC crosslinked body that has undergone a core crosslinking reaction step with a surface crosslinking agent to obtain a CMC having a core-shell structure.
[0011] Another object of the present invention is to provide CMC particles produced by said method and absorbent articles containing the same. [Means for solving the problem]
[0012] One embodiment of the present invention provides a method for producing CMC particles, including: (1) a step of reacting a cellulose raw material with an alkalizing agent to obtain alkalized cellulose; (2) a step of reacting the alkalized cellulose with a carboxymethylating agent to obtain CMC; (3) a primary crosslinking step of reacting the CMC with a core crosslinking agent to obtain a slurry-state CMC crosslinked body; (4) a step of filtering the slurry-state CMC crosslinked body, washing and dehydrating it; (5) a secondary crosslinking step of reacting the CMC crosslinked body that has undergone the step (4) with a surface crosslinking agent to obtain a CMC having a core-shell structure; and (6) a step of drying and pulverizing the CMC having a core-shell structure to obtain CMC particles having a core-shell structure.
[0013] Another embodiment of the present invention provides CMC particles produced by the above-mentioned production method.
[0014] Another embodiment of the present invention provides an absorbent article comprising the CMC particles produced by the above-mentioned production method. Effect of the Invention
[0015] According to the present invention, modified CMC particles having high absorbency can be produced by reacting the CMC crosslinked body that has undergone the core crosslinking reaction step with a surface crosslinking agent to obtain a CMC having a core-shell structure.
[0016] The CMC particles thus prepared can have excellent gel strength and AUL due to surface cross-linking, and can exhibit excellent blood absorption due to the improvement in bulk density obtained through the secondary cross-linking step. Furthermore, according to the present invention, it is possible to provide CMC particles having excellent water retention capacity measured under harsh conditions, for example, CRC, which indicates the amount of water retention of saline measured after centrifugation. Therefore, the CMC particles according to the present invention can be preferably used in feminine products for blood absorption.
[0017] In addition, according to the present invention, since gelation of CMC does not proceed during the core crosslinking process, the problem of non-uniform crosslinking due to high viscosity caused during this process can be eliminated. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a photograph of blood applied to the CMC particles prepared in Example 1. [Diagram 2] FIG. 2 is a photograph of the Petri dish of FIG. 1 after the CMC particles that had not come into contact with blood had been shaken off. [Diagram 3] FIG. 3 is a photograph of blood applied to the CMC particles prepared in Example 8. [Figure 4] FIG. 4 is a photograph of the Petri dish of FIG. 3 after the CMC particles that had not come into contact with blood had been shaken off. [Diagram 5] FIG. 5 shows the apparatus for measuring the AUL of CMC particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will now be described in detail.
[0020] In this specification, when a part "comprises" a certain component, this does not mean that it excludes other components, but that it may further include other components, unless specifically stated to the contrary.
[0021] As used herein, the term "core crosslink" refers to a crosslink formed in the CMC main chain by the reaction of CMC with a crosslinking agent, the crosslinking agent used in this case is referred to as a "core crosslinking agent," and the reaction between the CMC and the core crosslinking agent is referred to as a "core crosslinking reaction."
[0022] In this specification, the term "surface crosslinking (or shell crosslinking)" means a crosslink formed on the surface of a CMC crosslinked body by a reaction between a CMC crosslinked body having a core crosslink and a crosslinking agent, the crosslinking agent used in this case is called a "surface crosslinking agent (or shell crosslinking agent)", and the reaction between the CMC crosslinked body and the surface crosslinking agent is called a "surface crosslinking reaction".
[0023] One embodiment of the present invention provides a method for producing CMC particles, including: (1) a step of reacting a cellulose raw material with an alkalizing agent to obtain alkalized cellulose; (2) a step of reacting the alkalized cellulose with a carboxymethylating agent to obtain CMC; (3) a primary crosslinking step of reacting the CMC with a core crosslinking agent to obtain a slurry-state CMC crosslinked body; (4) a step of filtering the slurry-state CMC crosslinked body, washing and dehydrating it; (5) a secondary crosslinking step of reacting the CMC crosslinked body that has undergone the step (4) with a surface crosslinking agent to obtain a CMC having a core-shell structure; and (6) a step of drying and pulverizing the CMC having a core-shell structure to obtain CMC particles having a core-shell structure.
[0024] Hereinafter, the method for producing CMC particles according to the present invention will be described in detail step by step.
[0025] (1) The step of obtaining alkalized cellulose (alkalization reaction step)
[0026] In this step, the cellulose raw material is reacted with an alkalizing agent to obtain alkalized cellulose.
[0027] As the cellulose raw material, conventional pulps generally used in this field can be used without any length restrictions, specifically, pulps of 1 μm to 8 mm can be used, more specifically, pulps of 0.15 mm to 0.5 mm can be used. More specifically, the cellulose raw material may be prepared by cutting at least one pulp selected from the group consisting of raw cotton, linter, and wood to a length of 0.15 mm to 0.5 mm. When using the cut cellulose raw material, entanglement between the cellulose raw material and the mixer is reduced, and the generation of lumps due to fine pulp is suppressed, allowing for a uniform reaction, reducing the working time, and improving productivity by ensuring workability and fluidity. As a result, it is possible to reduce the manufacturing cost by 30% or more compared to the case of using a cellulose raw material that has not been cut.
[0028] The step of obtaining the alkalized cellulose may be performed by a conventional method generally used in this field. For example, a method may be used in which the cellulose raw material and the reaction solvent are introduced into a reactor, and then the alkalization agent is introduced therein, and the mixture is reacted at a temperature of 20° C. to 30° C. for 90 to 150 minutes while stirring at a speed of 100 rpm to 200 rpm to convert the cellulose into the alkalized cellulose.
[0029] The reaction solvent may include at least one selected from the group consisting of water, acetone, isopropyl alcohol, tert-butyl alcohol, and dimethyl ether, and the amount of the reaction solvent used may be 50 parts by weight or more and 2,000 parts by weight or less based on 100 parts by weight of the cellulose raw material.
[0030] The alkalizing agent may include an alkali metal hydroxide. For example, the alkalizing agent may include one or more selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide, and may be used in the form of an aqueous solution. The amount of the alkalizing agent added may be 5 parts by weight or more and 600 parts by weight or less with respect to 100 parts by weight of the cellulose raw material. When the amount of the alkalizing agent added is within the above range, the carboxymethyl group may be uniformly substituted throughout the cellulose in the step (2) described below, and the reactivity of the carboxymethylating agent may be increased to obtain a CMC with a desired degree of substitution.
[0031] The purpose of adding the alkalizing agent is to weaken the crystal structure of cellulose so that the cellulose can easily react with the carboxymethylating agent described below. That is, the alkalizing agent serves to promote the reaction between the cellulose and the carboxymethylating agent. The crystal structure of the alkalized cellulose can be uniformly weakened by stirring for a certain period of time at room temperature (20°C to 30°C).
[0032] (2) Step of obtaining CMC (carboxymethylation reaction step)
[0033] In this step, the alkalized cellulose obtained in step (1) is reacted with a carboxymethylating agent to obtain CMC.
[0034] The step of obtaining CMC may be carried out by a method generally used in this field, for example, a method of adding a carboxymethylating agent to a reactor containing the alkalized cellulose obtained by the step (1) and then reacting the carboxymethylating agent at elevated temperature may be used.
[0035] According to one embodiment of the present invention, the step (2) may include: (2-1) a first carboxymethylation reaction step carried out at 40° C. to 55° C. for 90 to 150 minutes; and (2-2) a second carboxymethylation reaction step carried out at 65° C. to 75° C. for 30 to 90 minutes.
[0036] Specifically, the carboxymethylating agent may include any one selected from chloroacetic acid, chloroacetic acid sodium salt, and a mixture thereof, and may be used in the form of a mixed solution dissolved in a reaction solvent, where the reaction solvent may include at least one selected from the group consisting of water, acetone, isopropyl alcohol, tert-butyl alcohol, and dimethyl ether.
[0037] According to one embodiment of the present invention, the degree of substitution (DS) of the carboxymethyl group of the CMC prepared by step (2) may be 0.7 to 2.0, and the degree of polymerization (DP) of the CMC may be 800 to 4,000. In this specification, the degree of substitution (DS) of the carboxymethyl group means the average number of hydroxyl groups substituted with a carboxymethyl group per anhydroglucose unit in a cellulose molecule, and when the degree of substitution (DS) of the carboxymethyl group is within the above range, it is preferable because a uniform reaction can be performed. In addition, the degree of polymerization of the CMC is a factor that affects the viscosity of the CMC, and when the degree of polymerization is within the above range, it is preferable because CMC particles having excellent volume density can be produced.
[0038] According to one embodiment of the present invention, the method may further include (2.5) neutralizing the CMC obtained in step (2) before the step (3) described below. The neutralization step may be carried out by a conventional method commonly used in this field, for example, neutralizing the CMC by adding a neutralizing agent. Here, any oxidizing agent may be used as the neutralizing agent, for example, nitric acid, acetic acid, hydrochloric acid, etc. are mainly used, and these may be used in the form of an aqueous solution diluted to a concentration of 40% by weight or more and 99% by weight or less.
[0039] (3) Primary crosslinking step (core crosslinking reaction step)
[0040] In this step, the CMC obtained in step (2) is reacted with a core crosslinking agent to obtain a crosslinked CMC in a slurry state. Here, the slurry state refers to a liquid state with low fluidity containing a high concentration of suspended solids (crosslinked CMC), and gelation does not proceed in this step.
[0041] The steps (1) to (3) may be performed continuously or discontinuously. For example, when the steps (1) to (3) are performed continuously in the same reactor, the reactor after the step (2) may contain CMC in which the carboxymethylation reaction has been completed or is in progress, and the core crosslinking agent may be added thereto to perform the core crosslinking reaction continuously. That is, according to the present invention, after the step (2) (carboxymethylation reaction step), the core crosslinking agent is added to the reactor containing the wet type CMC without a separate drying or grinding process, and the wet type CMC participates in the core crosslinking reaction to form a CMC crosslinked body. Through the reaction of the wet type CMC with the core crosslinking agent, a core crosslink is formed in the backbone of the CMC, and thus a CMC crosslinked body in a slurry state can be obtained.
[0042] Meanwhile, when steps (1) to (3) are performed discontinuously, a drying and grinding process can be performed after step (2), and the dry type CMC and core crosslinking agent that have undergone this process and the reaction solvent can be fed into a reactor. Then, a core crosslink is formed in the backbone of the CMC through the reaction of the CMC and the core crosslinking agent in the reactor, thereby obtaining a CMC crosslinked body in a slurry state.
[0043] In this case, it is preferable to perform the steps (1) to (3) continuously in the same reactor, since the process is simpler and more economical than to perform them discontinuously. The CMC to which the core crosslinking is applied can ensure dispersibility and absorbency in 0.9% saline solution.
[0044] According to one embodiment of the present invention, the core crosslinker may include at least one selected from the group consisting of an epoxy compound and a polyhydric alcohol. Specific examples of the epoxy compound include epichlorohydrin, glycerol diglycidyl ether, polyethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and glycidol. Examples of the polyhydric alcohol include glycerin, glycerol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, and propylene glycol. Examples of suitable glycols include dipropylene glycol, polypropylene glycol, and the like.
[0045] According to one embodiment of the present invention, the content of the core crosslinking agent may be 0.1 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the cellulose raw material. When the content of the core crosslinking agent is within the above range, the efficiency of the core crosslinking reaction is excellent and a suitable core crosslinking density is exhibited, so that the Centrifuge Retention Capacity (CRC) of the finally provided CMC particles can be improved.
[0046] According to one embodiment of the present invention, step (3) may be carried out at 65°C to 75°C for 30 to 90 minutes with stirring at a speed of 100 rpm to 300 rpm. When the reaction temperature, reaction time and stirring speed are within the above ranges, gelation does not proceed and core crosslinking proceeds, and the crosslinking reaction efficiency is high compared to the energy input, making it economical. In addition, step (3) may be carried out under a pH condition of 6 to 8, in which case the crosslinking reaction is easily controlled and the crosslinking reaction efficiency can be improved.
[0047] (4) Filtration, washing and dehydration stage
[0048] In this step, the crosslinked CMC in a slurry state obtained in step (3) is filtered, washed, and dehydrated.
[0049] Specifically, the crosslinked CMC in a slurry state obtained in step (3) may be filtered by a commonly known filtration method after being discharged from the reactor, for example, sieve filtration, suction filtration, ultrafiltration, filter press, etc., specifically, suction filtration may be used, but is not limited thereto.
[0050] According to one embodiment of the present invention, the washing in step (4) may be performed using at least one selected from the group consisting of water and a hydrophilic volatile organic solvent, and specifically, an aqueous solution containing a hydrophilic volatile organic solvent may be used. The hydrophilic volatile organic solvent is not particularly limited, and specific examples thereof include lower alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and tert-butyl alcohol; ketones such as acetone and methyl ethyl ketone; ethers such as 1,4-dioxane and tetrahydrofuran; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. More specifically, methanol, ethanol, or isopropyl alcohol may be used. Through the washing process, impurities are removed and a crosslinked CMC with a purity of 99% or more can be obtained.
[0051] (5) Secondary cross-linking step (surface cross-linking reaction step)
[0052] In this step, the CMC crosslinked product obtained in step (4) is reacted with a surface crosslinking agent to obtain a CMC having a core-shell structure.
[0053] According to one embodiment of the present invention, the surface cross-linking agent may include at least one selected from the group consisting of polyfunctional epoxy compounds and polyhydric alcohols. Specific examples of the epoxy compound include epichlorohydrin, glycerol diglycidyl ether, polyethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and glycidol. Examples of the polyhydric alcohol include glycerin, glycerol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, and propylene glycol. Examples of suitable glycols include dipropylene glycol, polypropylene glycol, and the like.
[0054] According to one embodiment of the present invention, the content of the surface crosslinking agent may be 0.1 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the CMC crosslinked product obtained through step (4). When the content of the surface crosslinking agent is within the above range, it is possible to provide CMC particles having excellent surface crosslinking reaction efficiency and good compression absorption capacity.
[0055] Meanwhile, in the method for producing CMC particles according to the present invention, in step (5), one of the following two methods may be used.
[0056] As a first method, the step (5) may be a secondary crosslinking step in which the crosslinked CMC obtained in the step (4) is reacted with the surface crosslinking agent and the foaming agent to obtain a porous CMC having a core-shell structure. In this case, the foaming agent and the surface crosslinking agent may react with the crosslinked CMC in a solution state. Specifically, in the step (5), a foaming agent solution and a surface crosslinking agent solution may be added to the crosslinked CMC, or a mixed solution of a foaming agent solution and a surface crosslinking agent solution may be added.
[0057] According to one embodiment of the present invention, the foaming agent may include a carbonate compound, and more specifically, may include one or more carbonate compounds selected from the group consisting of magnesium carbonate, calcium carbonate, sodium bicarbonate, and potassium bicarbonate. The foaming agent may be added in the form of an aqueous solution as a water-soluble compound.
[0058] According to one embodiment of the present invention, the content of the foaming agent may be 0.03 parts by weight to 20 parts by weight, specifically, 0.3 parts by weight to 15 parts by weight, based on 100 parts by weight of the CMC crosslinked body that has undergone step (4). When the content of the foaming agent is within the above range, it is possible to provide CMC particles having excellent blood absorption ability through improvement of the volume density.
[0059] In the first method, the surface crosslinking agent solution may contain a hydrophilic volatile organic solvent as a solvent. Examples of the hydrophilic volatile organic solvent include lower alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and tert-butyl alcohol; ketones such as acetone and methyl ethyl ketone; ethers such as 1,4-dioxane and tetrahydrofuran; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. Specifically, the hydrophilic volatile organic solvent may be an alcohol, and more specifically, the hydrophilic volatile organic solvent may be methanol, ethanol, or isopropyl alcohol.
[0060] According to one embodiment of the present invention, in the first method, step (5) may be performed at 50° C. to 90° C. for 120 to 270 minutes while stirring at a speed of 100 rpm to 300 rpm. When step (5) is performed under the above reaction conditions, the CMC crosslinked product, the foaming agent, and the surface crosslinking agent are uniformly distributed, and the surface crosslinking efficiency may be improved.
[0061] As a second method, the step (5) may be a secondary crosslinking step in which a surface crosslinking agent solution prepared by dissolving the surface crosslinking agent in an organic solvent and water are added to the carboxymethyl cellulose crosslinked body obtained by the step (4) to surface crosslink the carboxymethyl cellulose crosslinked body and simultaneously gel it, thereby obtaining carboxymethyl cellulose in a gel phase having a core-shell structure.
[0062] According to one embodiment of the present invention, in the second method, the organic solvent may include a hydrophilic volatile organic solvent having a boiling point lower than that of water, specifically, an alcohol having a boiling point lower than that of water. Examples of the hydrophilic volatile organic solvent having a boiling point lower than that of water include lower alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, and tert-butyl alcohol; ketones such as acetone; and ethers such as tetrahydrofuran. Examples of the alcohol having a boiling point lower than that of water include methanol, ethanol, and isopropyl alcohol.
[0063] According to one embodiment of the present invention, in the second method, the content of the organic solvent added in step (5) may be 200 parts by weight or more and 2,000 parts by weight or less based on 100 parts by weight of water. In step (5) (surface crosslinking reaction step), the relative amount of water and organic solvent is very important. Specifically, when the amount of organic solvent is relatively large compared to the amount of water at the beginning of the surface crosslinking reaction step, a rapid increase in viscosity due to CMC swelling can be suppressed, and thus uniform surface crosslinking can be performed. Thereafter, as the surface crosslinking reaction proceeds while the temperature is increased, the amount of organic solvent can become relatively smaller than the amount of water due to volatilization, and thus the surface crosslinking reaction of the CMC crosslinked body having the core crosslink proceeds, and at the same time, the CMC crosslinked body can swell and be hydrated with water to be gelled.
[0064] According to one embodiment of the present invention, in the second method, the step (5) may include a process of stirring at a speed of 100 rpm to 300 rpm for 120 minutes to 360 minutes while heating to a temperature of 100°C to 100°C to 50°C to 120 minutes. When the step (5) is performed under the above reaction conditions, the organic solvent having a boiling point lower than that of water may be volatilized first as the reaction progresses to the latter stage. According to the change in the solution balance of the organic solvent and water during the heating process, a uniform surface crosslinking reaction may proceed and gelation may occur at the same time. For example, when ethanol is used as the organic solvent, the solution balance is "amount of organic solvent>amount of water" below the azeotropic point of water and ethanol (78.1°C), and when the temperature is gradually raised to a temperature higher than the azeotropic point, it may change to "amount of water>amount of organic solvent". That is, in the initial stage of the temperature rise process (amount of organic solvent>amount of water), a uniform surface crosslinking reaction mainly occurs, and when the solution balance changes due to the temperature rise (amount of water>amount of organic solvent), gelation may gradually proceed along with the surface crosslinking reaction, thereby smoothly proceeding with the uniform surface crosslinking reaction, and a CMC having an excellent core-shell structure may be obtained. On the other hand, when CMC is crosslinked and gelled simultaneously in the presence of water alone without an organic solvent, the viscosity increases due to the rapid swelling of the CMC at the initial stage of the reaction, and thus a non-uniform crosslinking reaction may occur.
[0065] (6) Obtaining CMC particles
[0066] This step is a step of drying and pulverizing the CMC having a core-shell structure obtained in step (5) to obtain CMC particles having a core-shell structure. At this time, the CMC having a core-shell structure may be dried and pulverized after a dehydration process.
[0067] The drying may be performed using any commonly known drying method without limitation, such as natural drying, hot air drying, or high temperature drying.
[0068] The grinding may be carried out using a commonly known grinding machine, such as a cutting mill, a hammer mill, a pin mill, a screw mill, a roll mill, or a disc mill.
[0069] According to one embodiment of the present invention, the bulk density of the CMC particles having a core-shell structure obtained by step (6) may be 0.5 g / ml to 0.9 g / ml, in which case, particles with excellent blood absorption and dispersibility can be provided. In particular, when the bulk density is within the above range, when liquid is absorbed into an absorbent article containing the CMC particles, the gel blocking phenomenon caused by the particles rising to the upper layer of the absorbent article and the problem of reduced initial absorbency caused by the particles concentrating in the lower layer of the absorbent article can be eliminated.
[0070] The method for producing CMC particles according to the present invention may further include a classification step of sieving the porous CMC particles having a core-shell structure obtained in step (6) to obtain particles having a size of 150 μm to 850 μm. When the size of the CMC particles is within the above range, the gel blocking phenomenon caused by reduced dispersibility due to small particle size and the reduced absorbency caused by excessive liquid permeability due to large particle size can be eliminated. When considering both dispersibility and absorbency, the size of the CMC particles may be 250 μm to 500 μm.
[0071] Another embodiment of the present invention provides CMC particles produced by the above-mentioned production method and absorbent articles containing the same.
[0072] According to one embodiment of the present invention, the blood absorption capacity of the CMC particles calculated by the following formula may be 130 mg or more and 155 mg or less.
[0073] Calculation formula 1 Blood absorption capacity (mg) = W2 - W1
[0074] In the above formula 1, W1 is the weight of the Petri dish, and W2 is the weight of the Petri dish measured after 1.0 g of CMC particles are evenly placed in the Petri dish, 0.1 ml of blood is continuously dropped drop by drop in the center of the dish containing the CMC particles, the blood is allowed to clot at room temperature for 2 hours, and then all the clean CMC particles that were not in contact with the blood are shaken off.
[0075] As described above, the CMC particles produced by the present invention have excellent AUL, CRC and blood absorption, and therefore can be preferably used for female sanitary napkins, which are feminine products for absorbing blood.In addition, absorbent articles selected from the group consisting of disposable diapers, sanitary products such as adult urinary incontinence products, and pet products such as defecation pads can be produced, and can also be used in a variety of ways as materials for medical absorbents, water-stopping materials for civil engineering and construction, seedling sheets, and freshness-maintaining agents in the food distribution field. EXAMPLES
[0076] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples.
[0077] Example 1 First, pulp (Ethenier-F, manufactured by Rayonier) was cut into pieces having a length of 0.15 mm or more and 0.5 mm or less to prepare a cellulose raw material.
[0078] Then, 90 g of the cut cellulose raw material was added to a pressure reactor (Druvatherm series, manufactured by Lodige), 1231 g of an 80 wt% isopropyl alcohol aqueous solution as a reaction solvent was added, and then 158 g of a 50 wt% sodium hydroxide aqueous solution as an alkalizing agent was added. The mixture was reacted at 25°C for 120 minutes with stirring at 150 rpm to obtain alkalized cellulose.
[0079] Then, 360 g of 45 wt % sodium chloroacetate aqueous solution, which is a carboxymethylating agent, was added to the reactor to produce CMC. At this time, the CMC was produced through a first carboxymethylation reaction step in which the alkalized cellulose and the carboxymethylating agent in the reactor were reacted at 50°C for 120 minutes while stirring at a speed of 200 rpm, and then a second carboxymethylation reaction step in which the temperature was raised to 70°C and the reaction was carried out for 60 minutes. The degree of substitution (DS) of the carboxymethyl group of the CMC produced in this way was 1.0, and the degree of polymerization (DP) was 1,400.
[0080] Then, 4 g of glycerol diglycidyl ether, a core crosslinking agent, was added to the reactor containing the CMC, and the core crosslinking reaction (primary crosslinking reaction) was carried out at 70° C. for 60 minutes while stirring at a speed of 200 rpm to produce a crosslinked CMC in a slurry state. At this time, gelation of the crosslinked CMC was not performed.
[0081] Thereafter, the slurry-state CMC crosslinked body was discharged from the reactor and filtered with a suction filter (LK Lab Korea, WJ-110), and then 900 g of a 70 wt% ethanol aqueous solution was added for primary washing, and 900 g of an 80 wt% ethanol aqueous solution was added for secondary washing, followed by dehydration.
[0082] Then, 30 g of the crosslinked CMC that had undergone the dehydration process was transferred again to a pressure reactor, and 270 g of a 1 wt % polyethylene glycol diglycidyl ether solution (solvent: ethanol) and 90.45 g of a foaming agent aqueous solution obtained by dissolving 0.45 g of sodium bicarbonate (foaming agent) in 90 g of water were added thereto. The internal temperature of the reactor was then raised to 70°C, and a surface crosslinking reaction (secondary crosslinking reaction) was carried out at 70°C for 180 minutes while stirring at a speed of 150 rpm to produce a porous CMC having a core-shell structure.
[0083] After the surface cross-linking reaction was completed, the porous CMC having a core-shell structure was dehydrated, dried with hot air at 70°C for 360 minutes, and then pulverized with a cutting mill (Fritsch, Pulverisette 19) to produce porous CMC particles having a core-shell structure (hereinafter referred to as "particle 1"). At this time, the particle 1 has a particle size ranging from 250 μm to 500 μm. In addition, the particle 1 was obtained by sieving with a 60 mesh (250 μm) standard sieve to obtain particles having a size of 250 μm or more, and then sieving with a 35 mesh (500 μm) standard sieve to eliminate particles having a size exceeding 500 μm.
[0084] Example 2 CMC particles having a core-shell structure (hereinafter referred to as "particles 2") were produced in the same manner as in Example 1, except that 90.09 g of a foaming agent aqueous solution prepared by dissolving 0.09 g of sodium bicarbonate (foaming agent) in 90 g of water was added.
[0085] Example 3 CMC particles having a core-shell structure (hereinafter referred to as "particles 3") were produced in the same manner as in Example 1, except that 90.27 g of a foaming agent aqueous solution prepared by dissolving 0.27 g of sodium bicarbonate (foaming agent) in 90 g of water was added.
[0086] Example 4 CMC particles having a core-shell structure (hereinafter referred to as "particles 4") were prepared in the same manner as in Example 1, except that 90.9 g of a foaming agent aqueous solution prepared by dissolving 0.9 g of sodium bicarbonate (foaming agent) in 90 g of water was added.
[0087] Example 5 CMC particles having a core-shell structure (hereinafter referred to as "particles 5") were produced in the same manner as in Example 1, except that 94.5 g of a foaming agent aqueous solution prepared by dissolving 4.5 g of sodium bicarbonate (foaming agent) in 90 g of water was added.
[0088] Example 6 CMC particles having a core-shell structure (hereinafter referred to as "particles 6") were prepared in the same manner as in Example 1, except that the surface cross-linking reaction time was adjusted to 240 minutes.
[0089] Example 7 CMC particles having a core-shell structure (hereinafter, referred to as "particles 7") were prepared in the same manner as in Example 1, except that the second carboxymethylation reaction time was adjusted to 80 minutes.
[0090] Example 8 The non-gelled crosslinked CMC in a slurry state discharged from the reactor in Example 1 was filtered, washed and dehydrated in the same manner as in Example 1.
[0091] Then, 30 g of the crosslinked CMC after the dehydration process was transferred to a pressure reactor again, and 270 g of 1 wt % polyethylene glycol diglycidyl ether solution (solvent: ethanol) and 90 g of water were added thereto, and the internal temperature of the reactor was raised to 88° C., and the reactor was stirred at a speed of 150 rpm for 240 minutes to proceed with gelation simultaneously with the surface crosslinking reaction (secondary crosslinking reaction), thereby producing a gel phase CMC having a core-shell structure. At this time, the azeotropic point of ethanol and water, which are the solvents of the surface crosslinking agent solution, is 78.1° C., and below the azeotropic point, the amount of ethanol is greater than the amount of water in the reactor, and when the temperature is raised above the azeotropic point, the solution balance is changed and the amount of ethanol is less than the amount of water.
[0092] After the surface cross-linking reaction was completed, the gel phase CMC was dehydrated, dried with hot air, and pulverized in the same manner as in Example 1 to produce CMC particles having a core-shell structure and a size of 250 μm to 500 μm (hereinafter referred to as "particles 8").
[0093] Example 9 In the surface crosslinking reaction (secondary crosslinking reaction), the internal temperature of the reactor was raised to 88°C and stirred at a speed of 150 rpm for 300 minutes to carry out gelation simultaneously with the surface crosslinking reaction (secondary crosslinking reaction), thereby producing CMC in a gel phase having a core-shell structure. CMC particles having a core-shell structure (hereinafter referred to as "particles 9") were produced in the same manner as in Example 8, except that.
[0094] Example 10 After preparing CMC through the first and second carboxymethylation reaction steps, before proceeding with the core crosslinking reaction (first crosslinking reaction), the temperature of the reactor containing the CMC was cooled to 30°C, and 60 ml of 35% HCl solution was slowly added dropwise for 20 minutes to neutralize the pH to 8.5. CMC particles having a core-shell structure (hereinafter referred to as "particle 10") were prepared in the same manner as in Example 8.
[0095] Comparative Example 1 CMC particles having a core-shell structure (hereinafter referred to as "particles 11") were prepared in the same manner as in Example 1, except that 90 g of water without a foaming agent was added instead of the foaming agent aqueous solution.
[0096] Comparative Example 2 CMC particles having a core-shell structure (hereinafter referred to as "particles 12") were prepared in the same manner as in Comparative Example 1, except that the surface cross-linking reaction time was adjusted to 240 minutes.
[0097] Comparative Example 3 CMC particles having a core-shell structure (hereinafter, referred to as "particles 13") were prepared in the same manner as in Comparative Example 1, except that the secondary carboxymethylation reaction time was adjusted to 80 minutes.
[0098] Comparative Example 4 The crosslinked CMC in a slurry state discharged from the reactor in Example 8 was filtered, washed and dehydrated in the same manner as in Example 8, and then water was added and mixed therein to obtain a kneaded crosslinked CMC. At this time, the amount of water added was 1,000 parts by weight based on 100 parts by weight of the crosslinked CMC in a slurry state that had been subjected to the dehydration process.
[0099] The kneaded CMC crosslinked body was then molded into a sphere having a diameter of 2 cm, dried in an oven at 70°C for 360 minutes, and pulverized with a cutting mill (Fritsch, Pulverisette 19) to produce a granular CMC crosslinked body. The granular CMC crosslinked body had a particle size ranging from 250 μm to 500 μm and had only core crosslinks.
[0100] Then, 30 g of the granular CMC crosslinked body was transferred again to a pressure reactor, and 270 g of a 1 wt % polyethylene glycol diglycidyl ether solution (solvent: ethanol) and 90 g of water, which are surface crosslinking agent solutions, were added thereto, and the surface crosslinking reaction was carried out by an immersion method. At this time, the surface crosslinking reaction temperature was 70° C., and the reaction time was 1,440 minutes. Here, the immersion method means a method in which the surface crosslinking is carried out in a state where the CMC crosslinked body is immersed in the polyethylene glycol diglycidyl ether solution and water without a stirring process.
[0101] After the surface cross-linking reaction was completed, the mixture was dehydrated, dried and pulverized in the same manner as in Example 8 to prepare CMC particles having a core-shell structure (hereinafter referred to as "particles 14").
[0102] Comparative Example 5 CMC particles having a core-shell structure (hereinafter referred to as "particles 15") were produced in the same manner as in Comparative Example 4, except that uncut pulp (length 8 mm or more) was used as the cellulose raw material, the reaction time of the first carboxymethylation reaction step was adjusted to 180 minutes, and the reaction time of the second carboxymethylation reaction step was adjusted to 120 minutes.
[0103] Comparative Example 6 A CMC crosslinked body having a core crosslink was prepared by carrying out the core crosslinking reaction, washing and dehydration processes in the same manner as in Comparative Example 4, except that uncut pulp (length 8 mm or more) was used as the cellulose raw material, the reaction time of the first carboxymethylation reaction step was adjusted to 180 minutes, and the reaction time of the second carboxymethylation reaction step was adjusted to 120 minutes.
[0104] Thereafter, the CMC crosslinked body that had undergone the dehydration process was immediately dried with hot air at 70°C for 360 minutes without the surface crosslinking reaction step, and then pulverized with a cutting mill (Fritsch, Pulverisette 19) to produce CMC particles having only core crosslinks (hereinafter referred to as "particles 16").
[0105] <Evaluation method> 1. Blood absorption capacity The blood absorption capacity of particles 1 to 16 obtained in Examples 1 to 10 and Comparative Examples 1 to 6, respectively, was evaluated as follows.
[0106] First, the weight (W1) of a Petri dish with an inner diameter of 3 cm was measured, 1.0 g of particles was placed in the Petri dish, and the bottom was tapped lightly to uniformly distribute the particles on the surface of the dish. Then, 0.1 ml of blood was placed in a 1 ml plastic syringe, and a 21 G needle was used to slowly drop one drop at a time into the center of the particles in the Petri dish. Horse blood was used as the blood. Then, the blood was allowed to clot at room temperature for 2 hours, and all clean particles that had not come into contact with the blood were shaken off, and the weight (W2) of the Petri dish with the clotted blood and the particles remaining thereon was measured. The blood absorption capacity was calculated using the measured weight according to the following formula (1), and the results are shown in Table 1 below.
[0107] Blood absorption capacity (mg) = W2 - W1 (1)
[0108] In equation (1), W1 is the weight of an empty Petri dish and W2 is the weight of a Petri dish containing clotted blood and clotted particles.
[0109] Specifically, Fig. 1 shows a photograph of blood applied to the CMC particles produced in Example 1, and Fig. 2 shows a photograph of the CMC particles that have not come into contact with blood after being shaken off from the Petri dish in Fig. 1. Fig. 3 shows a photograph of blood applied to the CMC particles produced in Example 8, and Fig. 4 shows a photograph of the CMC particles that have not come into contact with blood after being shaken off from the Petri dish in Fig. 3.
[0110] 2. Absorbency Under Load (AUL) The pressurized absorbency of particles 1 to 16 obtained in Examples 1 to 10 and Comparative Examples 1 to 6, respectively, was measured using an apparatus as shown in FIG.
[0111] First, a 400 mesh metal mesh 5 was attached to the bottom of a cylindrical PMMA (polymethyl methacrylate) cylinder 7 (inner diameter: 60 mm, height: 50 mm). 0.9 g (W3) of the particles 6 were evenly placed on the metal mesh 5 at room temperature, and a plastic piston 8 equipped with a 0.7 psi metal weight 9 was placed on top of the particles 6 to configure an AUL measurement device.
[0112] Then, a glass ceramic filter plate 2 (diameter: 80 mm, thickness: 7 mm) with porosity #0 was placed inside a Petri dish 1 (diameter: 118 mm, height: 12 mm), and physiological saline solution 3 composed of a 0.9 wt % sodium chloride aqueous solution was poured into it so that it was at the same height as the ceramic filter plate 2, and then a filter paper 4 was placed on top of the ceramic filter plate 2.
[0113] Then, the AUL measuring device was placed on the filter paper 4 and physiological saline was absorbed under pressure for 60 minutes, and the weight (W4) of the particles in the measuring device was measured. The weight thus measured was used to calculate the AUL according to the following formula (2), and the results are shown in Table 1 below.
[0114] AUL(g / g) = (W4 - W3) / W3 (2)
[0115] In the above formula (2), W3 is the initial particle weight (0.9 g), and W4 is the particle weight after absorbing saline under pressure (0.7 psi) for 60 minutes.
[0116] 3.Centrifuge Retention Capacity (CRC) The centrifugal water retention capacity of particles 1 to 16 obtained in Examples 1 to 10 and Comparative Examples 1 to 6, respectively, was measured as follows.
[0117] 0.2 g (W5) of each particle was evenly placed in a tea bag and sealed, and then soaked in physiological saline consisting of 0.9 wt% sodium chloride aqueous solution at room temperature for 30 minutes. Then, moisture was removed from the sealed tea bag using a centrifuge at 250G for 3 minutes, and the weight (W6) of the sealed tea bag was measured. The same soaking and centrifugation operations were also performed on a tea bag without particles, and its weight (W7) was measured. The CRC was calculated using the measured weights according to the following formula (3), and the results are shown in Table 1 below.
[0118] CRC(g / g)=(W6-W7-W5) / W5...(3)
[0119] In formula (3), W5 is the weight of the initial particles (0.2 g), W6 is the weight of the tea bag sealed with the particles after soaking and centrifugation, and W7 is the weight of the tea bag without the particles after soaking and centrifugation.
[0120] [Table 1]
[0121] Referring to Table 1, it can be seen that Particles 1 to 10 prepared in Examples 1 to 10 are superior in AUL, CRC and blood absorption capacity compared to Particles 11 to 16 prepared in Comparative Examples 1 to 6, and in particular, the blood absorption capacity is significantly superior. The above-disclosed examples of the present invention are intended to illustrate but not to limit the technical concept of the present invention, and the scope of the present invention should be interpreted according to the claims below, and all technical concepts within the scope equivalent thereto should be interpreted as being included in the scope of the present invention. [Explanation of symbols]
[0122] 1: Petri dish 2: Ceramic filter plate 3: Saline (NaCl solution) 4: Filter paper 5: Metal mesh 6: Superabsorbent particles 7: PMMA cylinder 8: Plastic piston 9: Metal weight
Claims
1. (1) reacting a cellulose raw material with an alkalizing agent to obtain alkalized cellulose; (2) reacting the alkalized cellulose with a carboxymethylating agent to obtain carboxymethyl cellulose; (3) a primary crosslinking step of reacting the carboxymethyl cellulose with a core crosslinking agent to obtain a carboxymethyl cellulose crosslinked body in a slurry state; (4) filtering the carboxymethyl cellulose crosslinked body in the slurry state, and then washing and dehydrating the same; (5) a secondary crosslinking step of reacting the carboxymethyl cellulose crosslinked product obtained in step (4) with a surface crosslinking agent to obtain carboxymethyl cellulose having a core-shell structure; and (6) drying and pulverizing the carboxymethyl cellulose having a core-shell structure to obtain carboxymethyl cellulose particles having a core-shell structure; The step (5) is a secondary crosslinking step of surface-crosslinking the crosslinked carboxymethyl cellulose product obtained by the step (4) by adding a surface crosslinking agent solution obtained by dissolving the surface crosslinking agent in an organic solvent and water to the crosslinked carboxymethyl cellulose product, and simultaneously gelling the crosslinked carboxymethyl cellulose product to obtain carboxymethyl cellulose in a gel phase having a core-shell structure.
2. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the cellulose raw material is prepared by cutting at least one pulp selected from the group consisting of raw cotton, linter, and wood to a length of 0.15 mm to 0.5 mm.
3. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the step (2) includes: (2-1) a first carboxymethylation reaction step carried out at 40° C. to 55° C. for 90 to 150 minutes; and (2-2) a second carboxymethylation reaction step carried out at 65° C. to 75° C. for 30 to 90 minutes.
4. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the degree of substitution (DS) of the carboxymethyl group of the carboxymethyl cellulose produced by step (2) is 0.7 to 2.0, and the degree of polymerization (DP) of the carboxymethyl cellulose is 800 to 4,000.
5. The method for producing carboxymethyl cellulose particles according to claim 1, further comprising the step of neutralizing the carboxymethyl cellulose obtained by the step (2) before the step (3).
6. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the core crosslinking agent comprises at least one selected from the group consisting of epoxy compounds and polyhydric alcohols.
7. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the content of the core crosslinking agent is 0.1 to 40 parts by weight based on 100 parts by weight of the cellulose raw material.
8. The method of claim 1, wherein the step (3) is carried out at 65° C. to 75° C. for 30 to 90 minutes while stirring at a speed of 100 rpm to 300 rpm.
9. 2. The method of claim 1, wherein in step (4), the washing is performed using at least one selected from the group consisting of water and hydrophilic volatile organic solvents.
10. The surface cross-linking agent is one selected from the group consisting of polyhydric epoxy compounds and polyhydric alcohols. The method for producing carboxymethylcellulose particles according to claim 1, characterized in that it contains at least one type of carboxymethylcellulose. Construction method.
11. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the content of the surface crosslinking agent is 0.1 to 40 parts by weight based on 100 parts by weight of the carboxymethyl cellulose crosslinked product obtained in step (4).
12. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the organic solvent comprises a hydrophilic volatile organic solvent having a boiling point lower than that of water.
13. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the organic solvent includes an alcohol having a boiling point lower than that of water.
14. 2. The method of claim 1, wherein the content of the organic solvent added in step (5) is 200 parts by weight to 2,000 parts by weight based on 100 parts by weight of water.
15. The method for producing carboxymethylcellulose particles according to claim 1, wherein the step (5) includes a process of stirring at a speed of 100 rpm to 300 rpm for 120 minutes to 360 minutes while heating to a temperature of 100° C. or higher than the boiling point of the organic solvent or the azeotropic point of water and the organic solvent.
16. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the volume density of the carboxymethyl cellulose particles obtained by step (6) is 0.5 g / ml to 0.9 g / ml.
17. Carboxymethyl cellulose particles, characterized by being produced by the production method according to any one of claims 1 to 16.
18. The carboxymethylcellulose particles according to claim 17, characterized in that the blood absorption capacity of the carboxymethylcellulose particles calculated by the following calculation formula 1 is 130 mg or more and 155 mg or less: Calculation formula 1 Blood absorption capacity (mg) = W 2 -W 1 In the above formula 1, W 1 is the weight of the Petri dish, and W 2 is the weight of the Petri dish measured by uniformly placing 1.0 g of carboxymethylcellulose particles in the Petri dish, continuously dropping 0.1 ml of blood drop by drop onto the center of the dish containing the carboxymethylcellulose particles, allowing the blood to clot at room temperature for 2 hours, and then shaking off all the clean carboxymethylcellulose particles that were not in contact with the blood.
19. An absorbent article comprising carboxymethyl cellulose particles produced by the method according to any one of claims 1 to 16.
Citation Information
Patent Citations
Water absorbing material, method for producing the same and water absorbing article
JP2005263858A
Water-absorbent polysaccharide and method for producing the same
JP2008503600A
Water-absorbing resin particle, method of producing water-absorbing resin particle and absorber
JP2015178099A
Biodegradable composting assistant, and production method thereof
JP2016052973A
Acidic superabsorbent polysaccharides
KR1020010105311A
